2014
DOI: 10.4081/aiua.2014.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of individuals consuming natural spring water and tap water in terms of urinary tract stone disease

Abstract: Objectives: To compare individuals consuming natural spring water and tap water in terms of presence of urinary tract stone disease. Patients and methods: Patients were divided into two groups on the basis of the type of water: tap water (Group I) vs natural spring water consumers (Group II). The two groups were compared in terms of presence of urolithiasis. In addition to the type of water consumed, participants were investigated in terms of age, sex, occupation, body mass index (BMI) and presence of hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…9 Other studies also indicate a higher prevalence of the disease in men. [10][11][12] In the present study, most of the patients' BMI was > 25 kg/cm 2 . Scales et al, in their study, asserted that the prevalence of kidney stones was higher in obese people than those with a normal weight.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…9 Other studies also indicate a higher prevalence of the disease in men. [10][11][12] In the present study, most of the patients' BMI was > 25 kg/cm 2 . Scales et al, in their study, asserted that the prevalence of kidney stones was higher in obese people than those with a normal weight.…”
Section: Discussionmentioning
confidence: 44%
“…6 Resorlu et al also showed that hypertension plays a significant role in developing kidney stones. 10 The daily consumption of water was less than 3 liters in most of our patients. However, in a 2002 study by Morton et al in the United States, it was stated that the risk of developing kidney stones was high in the people who consumed low amounts of fluids per day.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation